LINGUISTIC AND LITERARY ANALYSIS OF THE ENGLISH TRANSLATION OF ISAJON SULTON’S SHORT STORY “AVLIYO (THE SAINT)” - Sobirova, Guzaloy (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article examines the lexical and stylistic subtleties of literary translation between Uzbek and English through Isajon Sultan’s short story “Avliyo.” The study analyzes linguistic, syntactic, idiomatic, and stylistic features in the English translation, supported by illustrative examples. Particular attention is paid to word choice, sentence structure, and the preservation of cultural and national symbols. The translator’s task is emphasized as bringing the literary work to international readers while maintaining the author’s national identity, worldview, and spiritual essence. The central discussion focuses on conveying the story’s semantic and aesthetic depth without losing its cultural context or national color. The relevance of this research within comparative literature and translation studies lies in the growing importance — especially in the era of globalization — of introducing masterpieces of Uzbek literature to the world while preserving their distinctive national spirit through high-quality translation. Although the imagery, symbolism, and meaning of “Avliyo” have been widely discussed in Uzbek literary criticism, its English translation has not yet received detailed artistic and linguistic analysis. This article provides a comparative study of the translation based on principles of translation theory and stylistic analysis, aiming to identify, examine, and propose solutions to various cultural and linguistic challenges encountered in the process of literary translation.